Temporary jobs and job search effort in Europe - Lawrence M. Kahn (Institute for the Study of Labor (IZA), 2009)
Using longitudinal data on individuals from the European Community Household Panel (ECHP) for eight countries during 1995-2001, I investigate temporary job contract duration and job search effort. The countries are Belgium, Denmark, Finland, France, Italy, the Netherlands, Portugal and Spain. I construct a search model for workers in temporary jobs which predicts that shorter duration raises search intensity. Calibration of the model to the ECHP data implies that at least 59% of the increase in search intensity over the life a long term temporary job occurs in the last period. I then estimate regression models for search effort that control for human capital, pay, local unemployment, gender, and time and country fixed effects, I find that workers on temporary jobs indeed search harder than those on permanent jobs. Moreover, search intensity increases as temporary job duration falls, and at least 80% of this increase occurs on average in the shortest duration jobs. These results are robust to disaggregation by gender and country and to individual fixed effects. These empirical results are noteworthy, since it is not necessary to assume myopia or hyperbolic discounting in order to explain them, although the data clearly also do not rule out such explanations.
urn:nbn:de:101:1-20090304777
Keywords: J21; J23; 330; Job search; temporary jobs; Arbeitsuche; Befristeter Arbeitsvertrag; Arbeitsverhältnis; EU-Staaten